TERJEMAHAN MAKNA ISTILAH BUDAYA PADA SUBTITLE BAHASA INGGRIS FILM SOEKARNO - Cut Mayang Purnama Sari; Umar Mono; Syahron Lubis (BAHAS, 2018)
The translator makes a semantic adjustment as well as possible to complete the translation in translating the original meaning of SL into TL. The semantic adjustment is considered as semantic shifts. The shift of meaning occurs when there is a semantic gap caused by some cultural and conceptual differences between SL and TL. This research is a qualitative descriptive research using objective data in the form of a cultural terms contained in the subtitle of Soekarno's film. The cultural terms in the form of spoken language of Indonesian as the source language are translated into the form of English subtitle as a target language is qualified tobe a research as a product. There are 19 cultural terms (70,3%) data from 27 cultural terms as research data in SL which have specific meaning are dominantly translated into general meaning in  TL. Then, there is 2 (7.4%) data as generic – specific translation. And 6 (22,2%) data as spefic – specific translation. The translation is considered good, but the specific meaning of the SL cultural terms are conveyed only partially.